2022
DOI: 10.1007/s11356-021-17976-4
|View full text |Cite
|
Sign up to set email alerts
|

Carbon emissions index decomposition and carbon emissions prediction in Xinjiang from the perspective of population-related factors, based on the combination of STIRPAT model and neural network

Abstract: In the present study, the STIRPAT model was adopted to examine the impacts of several factors on dioxide emissions using the time series data from 2000 to 2019 in Xinjiang. The said factors included population aging, urbanization, household size, per capita GDP, number of vehicles, per capita mutton consumption, education level, and household direct energy consumption structure. Findings were made that the positive effects of urbanization, per capita GDP, per capita mutton consumption and education on carbon e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(13 citation statements)
references
References 85 publications
1
12
0
Order By: Relevance
“…To promote economic development, the local government chose an unsophisticated development approach in the early stage of development, using energy consumption as the driving force for economic growth, and although the effect of this approach has been significant, carbon emissions are growing rapidly 69 . The carbon emissions in Xinjiang have been increasing rapidly since 2000, with an average annual growth rate of 10.24% 70 .…”
Section: Discussionmentioning
confidence: 99%
“…To promote economic development, the local government chose an unsophisticated development approach in the early stage of development, using energy consumption as the driving force for economic growth, and although the effect of this approach has been significant, carbon emissions are growing rapidly 69 . The carbon emissions in Xinjiang have been increasing rapidly since 2000, with an average annual growth rate of 10.24% 70 .…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we selected the economic and export-related data of Jiangsu Province from 2001 to 2020, built a data model, analyzed the prediction results of GDP values by different forecasting methods, and explored the socioeconomic development trends [21,22]. e empirical results show that the deep learning neural network-based forecasting approach has higher forecasting value and lower forecasting error values than other traditional forecasting approaches, which can provide a basis and reference for macroeconomic regulation and control of the economy and has good practical significance [23]. In addition, a more indepth investigation based on the research of other scholars, through the analysis of GDP-related indicators, can effectively combine GDP and prior indicators, which improves the persuasive power of prediction results and has a very important role in socioeconomic forecasting [24].…”
Section: Discussionmentioning
confidence: 99%
“…Also, the influence of economic urbanization and technology on carbon emissions were considered to expanded STIRPAT model, and the empirical analysis of this model showed that GDP per capita and population size have positive impact on carbon emissions, and population urbanization, economic urbanization, and energy intensity have inhibitory effects on carbon emission (Liu et al 2021 ). On this basis, the STIRPAT model is applied to determine the drivers of carbon emissions in Xinjiang, and the application results showed that urbanization and per capita GDP have considerable beneficial impacts on carbon emissions (Chai et al 2022 ). Moreover, the drivers of building carbon emissions were explored according to the demand and supply and introduced six identified factors to establish different STIRPAT models, and the empirical analysis showed that the indirect emission intensity and building construction among six identified factors have the greatest impact on carbon emissions (Zhu et al 2022c ).…”
Section: Literature Reviewmentioning
confidence: 99%